1999
DOI: 10.1038/12027
|View full text |Cite
|
Sign up to set email alerts
|

p45SKP2 promotes p27Kip1 degradation and induces S phase in quiescent cells

Abstract: The F-box protein p45SKP2 is the substrate-targeting subunit of the ubiquitin-protein ligase SCFSKP2 and is frequently overexpressed in transformed cells. Here we report that expression of p45SKP2 in untransformed fibroblasts activates DNA synthesis in cells that would otherwise growth-arrest. Expression of p45SKP2 in quiescent fibroblasts promotes p27Kip1 degradation, allows the generation of cyclin-A-dependent kinase activity and induces S phase. Coexpression of a degradation-resistant p27Kip1 mutant suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
562
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 647 publications
(592 citation statements)
references
References 43 publications
25
562
2
3
Order By: Relevance
“…Notably, expression of Skp2 was enhanced in all four human melanoma cell lines compared to NHEM (Figure 4a). Two Skp2 immunoreactive bands were observed consistent with others' reports Sutterluty et al, 1999;Garriga et al, 2003). We have previously shown that serum-starved NHEM express high levels of p27 Kip1 that are downregulated in an adhesion and growth factor-dependent manner (Bhatt et al, 2005).…”
Section: Skp2 Expression Is Enhanced In Melanoma Cells and Downregulasupporting
confidence: 90%
See 3 more Smart Citations
“…Notably, expression of Skp2 was enhanced in all four human melanoma cell lines compared to NHEM (Figure 4a). Two Skp2 immunoreactive bands were observed consistent with others' reports Sutterluty et al, 1999;Garriga et al, 2003). We have previously shown that serum-starved NHEM express high levels of p27 Kip1 that are downregulated in an adhesion and growth factor-dependent manner (Bhatt et al, 2005).…”
Section: Skp2 Expression Is Enhanced In Melanoma Cells and Downregulasupporting
confidence: 90%
“…p27 Kip1 levels in melanoma cells are also regulated by the proteasome. Phosphorylation at threonine 187 is permissive for p27 Kip1 degradation (Vlach et al, 1997;Carrano et al, 1999;Sutterluty et al, 1999). However, as threonine 187-phosphorylated p27 Kip1 levels increased in parallel with total p27 Kip1 (data not shown), we focused on possible defects in the SCF complex containing Skp2 and its cofactor, Cks1, that recognizes phosphorylated p27 Kip1 and targets it for degradation (Ganoth et al, 2001;Spruck et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCF Skp2 was identified as the E3 that targets p27 phosphorylated on Thr-187 for ubiquitination [21][22][23]. SCF complexes represent an evolutionarily conserved class of E3 enzymes containing four subunits: Skp1, Cul1, one of many F-box proteins and Roc1/Rbx1 (reviewed in [24]).…”
Section: Regulation Of P27 Protein Levelsmentioning
confidence: 99%